Pengembangan Aplikasi Smart Coffee Roaster berbasis IoT untuk Pengendalian dan Monitoring Proses Penyangraian Kopi - Aris Munandar; Oka Mahendra; Jony Winaryo Wibowo (Ikatan Ahli Informatika Indonesia, 2025)
The coffee roasting process plays a crucial role in determining flavor quality; therefore, a system that ensures consistency and easy replication of roasting profiles is required. This study developed a smartphone-based Smart Coffee Roaster integrated with an ESP32 microcontroller to support manual and automatic roasting control and monitoring. The system was designed to record and store roasting profiles, synchronize parameters with the ESP32 device, and display temperature and roasting stages in real time. The hardware was designed using relay modules and an ESP32 microcontroller, while the software was developed using Kodular and Arduino IDE. The system was tested using black-box methods and successfully executed all key functions, including profile selection, actuator control, and real-time visualization. The application simplified the monitoring and control of the roasting process and provided structured profile data to maintain coffee quality consistency and support further analysis based on artificial intelligence